Use of rocuronium and sugammadex under neuromuscular transmission monitoring in a patient with multiple sclerosis - Chryssoula Staikou; Martina Rekatsina (Saudi Journal of Anaesthesia, 2017)
Multiple sclerosis (MS) is a potentially disabling disease characterized by demyelinating lesions in the central nervous system. One of the anesthetic challenges encountered in surgical patients with MS is the management of neuromuscular blockade (NMB) and its reversal. We report a case of a 31-year-old female patient suffering from MS, who underwent gynecological surgery under general anesthesia with sevoflurane, fentanyl, and rocuronium which was successfully reversed with sugammadex. Neuromuscular transmission (NMT) monitoring was used to guide the intraoperative doses of rocuronium and also the reversal of NMB by the use of sugammadex to ensure a safe tracheal extubation. In addition, delivered volatile was titrated according to anesthetic depth monitoring (Bispectral Index) while esophageal temperature was also monitored for the maintenance of normothermia. Postoperatively, a multimodal analgesic scheme offered a high-quality analgesia and sleep, minimization of anxiety, and increased patient satisfaction. At 1-month follow-up, the patient's course was uncomplicated without any MS exacerbation. We consider that the use of rocuronium and sugammadex under NMT monitoring may represent a useful and safe choice in patients with MS.